2008
DOI: 10.1176/appi.ps.59.8.878
|View full text |Cite
|
Sign up to set email alerts
|

Employment Outcomes of Persons With a Mental Disorder and Comorbid Chronic Pain

Abstract: Objective-We sought to examine the independent and interactive effects of common mental health disorders and chronic pain conditions on employment and work outcomes among individuals younger than 65 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Unemployment was identified as a predictor of worse outcome across all outcome domains. Research suggests that unemployment is associated with greater emotional distress (Brown et al., ; Daly & Delaney, ; Paul & Moser, ) and higher disability in the general population (Moffett, Underwood, & Gardiner, ) and with depression in those with chronic pain (Braden, Zhang, Zimmerman, & Sullivan, ; Valkanoff, Kline‐Simon, Sterling, Campbell, & Von Korff, ). Further, employment supports behavioural engagement, provides a sense of achievement, is linked to better economic status and is a marker of positive behavioural capacities and skills (McKee‐Ryan, Song, Wanberg, & Kinicki, ; Tiggemann & Winefield, ; Waddell & Burton, ).…”
Section: Discussionmentioning
confidence: 99%
“…Unemployment was identified as a predictor of worse outcome across all outcome domains. Research suggests that unemployment is associated with greater emotional distress (Brown et al., ; Daly & Delaney, ; Paul & Moser, ) and higher disability in the general population (Moffett, Underwood, & Gardiner, ) and with depression in those with chronic pain (Braden, Zhang, Zimmerman, & Sullivan, ; Valkanoff, Kline‐Simon, Sterling, Campbell, & Von Korff, ). Further, employment supports behavioural engagement, provides a sense of achievement, is linked to better economic status and is a marker of positive behavioural capacities and skills (McKee‐Ryan, Song, Wanberg, & Kinicki, ; Tiggemann & Winefield, ; Waddell & Burton, ).…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Although recent advances have increased our understanding of treatment efficacy for chronic pain, about 40% of individuals report inadequate pain relief. 7 Many individuals suffer from the negative effects of chronic pain, such as frequent absence from work and unemployment, 6,19 limitations in physical activities, 54 disability, 47 decreased social interactions and/or perceived support, 9,12 depression, 35 and anxiety. 39 Research has consistently found a higher risk of the adverse effects of chronic pain in vulnerable populations, including racial/ethnic minorities 5,20 and individuals with low socioeconomic status.…”
mentioning
confidence: 99%
“…Patients with comorbidity of mental disorders and painful physical symptoms show more emotional distress, poorer physical functioning and lower rates of help seeking [ 7 ]. They also have worse prospects in the labor market and more financial problems and disability [ 43 ]. Overall pain scores were higher in those who had changed jobs or stopped doing jobs or going to school due to depression or injury.…”
Section: Discussionmentioning
confidence: 99%